Effect of direction of training los in accordance with the limitations of biorhythm on the level of special motor skills and skill performance of motor package (kata) in the players of the Egyptian national karate team - Abdelker, R. (International Journal of Sports Science and Arts, 2019)
Aim of the study: Identification of the effect of using biorhythm track limitations to direct the training los of motor skills on the level of motor package "kata" performance of the Egyptian karate players. Conclusions: 1- Improvement of special motor skills of "Kata" under study in the player of the study. The lowest percentage of improvement between the post measurement and pre measurement in the speed force test of right straight reverse punch (Gayku. Zuki) and was (8.33%), while the highest percentage of improvement between the pre and post measurements in the test of front right kick (Mae. Geri) was (50.00%) without biorhythm curves were used. 2- Improvement of motor skill of "kata" under study in the player of the study. The lowest percentage of improvement between the pre and post measurements was the lowest in the speed force test of the straight reverse right punch (Gayku. Zuki), and was (15.38%), while the highest percentage of improvement between the pre and post measurements was in the front right kick test (Mae. Geri) and was (60.00%) using biorhythm curves. 3- Performance of individual skill styles of "Kata" under study improved in the player of the study. The lowest percentage of improvement between the pre and post measurements of the skill style of right one-finger spear-hand (Ippon. Nukite) and was (3.39%), while the highest percentage of improvement was between the pre and post measurements of the performance of skill style of straight reverse right punch (Gayku. Zuki) and the skill style of finger one-finger spear-hand (Ippon. Nukite) and was (8.77%) without using biorhythm curves. 4- Performance standard of individual skill styles of "Kata" under study improved in the player of the study. The lowest percentage of improvement between the pre and post measurements of performance standard of skill style of straight long right punch (Oi. Zuki) and was (9.52%). The highest percentage of improvement between the pre and post measurements of performance standard of skill style of front right punch (Mae. Geri) improved and was (14.75%) using the biorhythm curves. 5- Performance standard of training packages of motor skills "Kata" under study improved in the player of the study. The lowest percentage of improvement between the pre and post measurements of the performance standard of first training package (3.39%), while the highest percentage of improvement between the pre and post measurements of the second training package performance standard was (8.62%) without using biorhythm curves. 6- Performance standard of training sections of motor package (Kata) under study improved in the player of the study. The lowest percentage of improvement between the pre and post measurements of the second training section performance standard improved and was (7.94%). The highest percentage of improvement between the pre and post measurements of the third training section performance standard improved and was (14.75%) using biorhythm curves. 7- Time and standard of performance of "Kata" under study improved in the player of the study. The percentage of improvement between the pre and post measurements was (1.67%) and (5.17%) respectively, without use of biorhythm curves. 8- Time and performance standard of motor package "Kata" under study improved in the player of the study. The percentage of improvement between the pre and post measurements was (4.17%) and (16.39%), respectively, using biorhythm curves